Menangani Luka, Menghindari Jerat: Tinjauan Sistematis tentang Strategi Coping Remaja dalam Konteks Kenakalan - Desyanadia Putri; Mira Ariyani; Zarina Akbar (Nathiqiyyah, 2026)
Juvenile delinquency is a multifaceted and evolving social phenomenon shaped by psychosocial stressors, dysfunctional family environments, and unsupportive social contexts. In response to these pressures, adolescents employ various coping strategies as forms of psychological defense. This study conducts a Systematic Literature Review (SLR) to examine the coping strategies used by delinquent adolescents and the effectiveness of coping-based interventions in reducing deviant behavior. Utilizing PRISMA guidelines and a PICO framework, 14 relevant articles published between 2019 and 2025 were systematically analyzed. The synthesis indicates that adaptive coping—such as problem-focused strategies, social support, and active engagement—contributes to improved psychological well-being and reduced delinquent behavior. Conversely, maladaptive coping, including avoidance, withdrawal, and denial, tends to exacerbate psychological distress and increase the risk of misconduct. Gender differences also emerge, with males more likely to rely on avoidance strategies and females more inclined to seek social support. Coping-based interventions, including Compassion-Focused Therapy and the Good Lives Model, demonstrate effectiveness in enhancing emotional regulation and fostering motivation for behavioral change. Nevertheless, limitations remain in long-term evaluation and the lack of culturally contextualized approaches. Future efforts should focus on developing adaptive, evidence-based interventions that support adolescents’ psychological well-being holistically and sustainably. Keywords : coping strategies, juvenile delinquency, adaptive coping, maladaptive coping, psychosocial interventions